Molecular characterization and in vitro control measures of fruit rot disease of Sweet pepper - Mallik, MRI; Sikder, MM; Hossain, MK; Billah, MB; Alam, N (International Journal of Agricultural Research, Innovation and Technology, 2022)
Fruit rot disease of sweet pepper is one of the main fungal diseases causing huge economic losses to the grower. An experiment was conducted to find out the fungal pathogen associated with fruit rot disease of sweet pepper, obtained from experimental fields of Jahangirnagar University, Bangladesh. Fruit rot disease-causing fungus was isolated from infected fruits and identified using morphological characterization based on colony features, mycelia, conidia as well as molecular characterization based on internal transcribe spacer (ITS) region of the fungus. ITS sequence of our studied fungus MH368146.1 was genetically 99-100% similar to sequences of Fusarium solani in NCBI database. Typical fruit rot symptoms were reproduced by artificial inoculations of the isolated fungus. The mycelial growth of this fungus was evaluated on ten different solid culture media i.e., Potato Dextrose Agar, Yeast Extract Agar, Honey Peptone Agar, Hansen’s Medium, Sabouraud’s Glucose Agar, Kauffman’s Agar, Potato Sucrose Agar, Richard’s Agar and Carrot Agar. Fungus grew well on all tested solid culture media. Several bio-control agents and two commercial fungicides were evaluated against isolated fungus under in vitro condition, in which the highest percent inhibition of radial growth of the fungus was determined as 64.75% due to Trichoderma reesei isolate 2, and 60.63% by Tilt 250 EC (500 ppm) at 7 days post-incubation. Therefore, T. reesei was found as the most suitable to control the growth of F. solani under laboratory conditions. However, further pot and field trials needed to be confirmed the bio-control potential of it. Int. J. Agril. Res. Innov. Tech. 11(2): 108-116, Dec 2021